LECTURERS' PERCEPTIONS OF SPIRITUAL LEADERSHIP: A QUANTITATIVE DESCRIPTIVE STUDY IN HIGHER EDUCATION (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas PGRI Mahadewa Indonesia, 2024)
Spiritual leadership has been recognized as holistic leadership that prioritizes spiritual aspects in managing the complex and dynamic academic environment. However, its implementation remains challenging. This study aimed to comprehensively understand lecturers' perceptions of spiritual leadership in higher education institutions. The research method used was a descriptive quantitative design. Respondents consisted of 336 lecturers from various private higher education institutions in Bali determined through a proportional random sampling technique and analyzed using descriptive statistics. The findings demonstrate lecturers' perceptions of spiritual leadership in the very high category. The vision indicator received the most important focus of attention in motivating and directing lecturers' actions in achieving institutional objectives, while the aspects of altruistic love, hope/faith, meaning/calling, and membership indicate opportunities for deeper emphasis to develop leaders who are responsible, competent, and have integrity. The findings contribute to the importance of implementing spiritual leadership in developing a harmonious academic community and creating the spiritual well-being of lecturers to achieve the main performance of higher education institutions.